(untitled) - Koelsch, Frank (Toronto, 1994)
Author gives us powerful insights into how technology is reshaping our world. This book is a welcome survey from a seasoned observer and analyst of the collision of the world's most powerful industries - media, telecommunications, entertainment and technology.
Keywords: Telecommunication,Information networks